RAB27B requirement for stretch-induced exocytosis in bladder umbrella cells - Gallo, Luciana Ines (2017)
Umbrella cells, which must maintain a tight barrier, modulate their apical surface area during bladder filling by exocytosis of an abundant, subapical pool of discoidal- and/or fusiform-shaped vesicles (DFVs). Despite the importance of this trafficking event for bladder function, the pathways the promote DFV exocytosis remain to be identified. We previously showed that DFV exocytosis depends in part on a RAB11A-RAB8A-MYO5B network, but RAB27B is also reported to be associated with DFVs, and knockout mice lacking RAB27B have fewer DFVs. However, the RAB27B requirements for DFV exocytosis, and the relationship between RAB27B and the other umbrella cell-expressed RABs remains unclear. Using a whole-bladder preparation, we observed that filling-induced exocytosis of human growth hormone-loaded DFVs was significantly inhibited when RAB27B expression was down regulated using shRNA. RAB27A was also expressed in rat urothelium; however, RAB27A-specific shRNAs did not inhibit exocytosis, and the combination of RAB27A and RAB27B shRNAs did not significantly affect DFV exocytosis more than treatment with RAB27B shRNA alone. RAB27B and RAB11A showed a small degree of overlap when quantified using SQUASSH segmentation software, and expression of dominant-active or dominant-negative mutants of RAB11A or RAB8A, or expression of a RAB11A-specific shRNA, had no significant effect on the size, number, or intensity of RAB27B-positive DFVs. Likewise, treatment with RAB27B-specific shRNA had no effect on RAB11A-positive DFV parameters. We conclude that RAB27B, but not RAB27A, regulates DFV exocytosis in bladder umbrella cells in a manner that may be parallel to the previously described RAB11A-RAB8A-MYO5B pathway.